2004
DOI: 10.1016/s0014-5793(04)00183-8
|View full text |Cite
|
Sign up to set email alerts
|

Important role of Ser443 in different thermal stability of human glutamate dehydrogenase isozymes1

Abstract: Molecular biological studies con¢rmed that two glutamate dehydrogenase isozymes (hGDH1 and hGDH2) of distinct genetic origin are expressed in human tissues. hGDH1 is heat-stable and expressed widely, whereas hGDH2 is heat-labile and speci¢c for neural and testicular tissues. A selective de¢-ciency of hGDH2 has been reported in patients with spinocerebellar ataxia. We have identi¢ed an amino acid residue involved in the di¡erent thermal stability of human GDH isozymes. At 45 ‡C (pH 7.0), heat inactivation proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 42 publications
(56 reference statements)
4
29
1
Order By: Relevance
“…It also indicates that the different sensitivities to alkalized extracts in the presence of high concentration of ADP may due to differences in the regulatory properties between hGDH isozymes by ADP. These observations are consistent with the previous reports that there are at least two different GDH activities differing in their relative thermal stability and allosteric regulation characteristics (Mavrothalassitis et al, 1988;Shashidharan et al, 1994;Cho et al, 2001;Yang et al, 2004). Since physiological ADP levels can vary from 0.05 to 1.0 mM depending on the rate of oxidative phosphorylation, our results suggest a possibility that hGDH1 and hGDH2 are differently regulated in vivo by the actions of alkalized extracts depending on the physiological concentrations of ADP.…”
Section: Protopinesupporting
confidence: 93%
See 1 more Smart Citation
“…It also indicates that the different sensitivities to alkalized extracts in the presence of high concentration of ADP may due to differences in the regulatory properties between hGDH isozymes by ADP. These observations are consistent with the previous reports that there are at least two different GDH activities differing in their relative thermal stability and allosteric regulation characteristics (Mavrothalassitis et al, 1988;Shashidharan et al, 1994;Cho et al, 2001;Yang et al, 2004). Since physiological ADP levels can vary from 0.05 to 1.0 mM depending on the rate of oxidative phosphorylation, our results suggest a possibility that hGDH1 and hGDH2 are differently regulated in vivo by the actions of alkalized extracts depending on the physiological concentrations of ADP.…”
Section: Protopinesupporting
confidence: 93%
“…Human GDH genes (pHGDH1 and pHGDH2) have been chemically synthesized, expressed in E. coli as soluble proteins, and homogeneously purified by the same methods developed in our laboratory as described elsewhere Lee et al, 2001;Yoon et al, 2002a;Yang et al, 2004). Y187M mutant at the ADP-binding site of the hGDH isozymes was constructed and homogeneously purified by the same methods developed in our laboratory as described elsewhere Yoon et al, 2002b).…”
Section: Methodsmentioning
confidence: 99%
“…Although this enzyme does not exhibit allosteric regulation in plants, bacteria, or fungi, its activity is tightly controlled by a number of compounds in mammals (1)(2)(3)(4)(5)(6). All mammalian GDHs are homohexameric, exhibiting 32 symmetry, and the first 200 residues form the core "glutamate binding" domain.…”
mentioning
confidence: 99%
“…Reciprocally interchanging amino acids that are different between hGDH isozymes within the regulatory domain may reveal the residues important for preference in hGDH isozymes. Recent studies of structure-function relationships using site-directed mutagenesis of hGDH1 at single sites differing from hGDH2 showed that the R443S and the G456A change reproduced some but not all of the properties of hGDH2 (3)(4)(5)17). In addition, several other residues differing between hGDH isozymes also have been examined by many investigators (4,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation